Socio-economic and Political Drivers of Renewable Natural Resource Conflicts among Crop Farmers in Southeast Nigeria - Chikaire, J.U; Atoma, C.N; Ajaero, J.O (Journal of Sustainability and Environmental Management, 2022)
The natural resource conflicts happen when there is variation on how natural resources and related ecosystems should be managed, owned, allocated, used, and protected. However, most researches on resource conflicts among different users, could not see the primacy of looking into these conflicts from the angle of their socio-economic and political causes. This paper among other things sought the socio-economic and political triggers of renewable natural resources conflict in Southeastern parts of Nigeria. Data were collected from 300 crop farmers purposively selected from three States - Imo, Abia and Enugu, using structured questionnaire and oral interview. Percentage and mean were used to analyze the collected data. The renewable natural resources considered in the study area were water, crop land, forests, and fishers/marine resources among others. The socio-political drivers of renewable resources conflict includes demand induced scarcity (87.7%), environmental degradation (83.3%), migration of people (91.6%) and unclear rights (85.3%). The study found that to reduce the occurrence of natural resource conflicts, following measures should be in place; reducing vulnerability to resources scarcity (M=3.57), increased availability of scarce resources (M=3.60), discourage/stop degradation (M=2.50), good governance framework (M=3.36) and effective resource sharing agreement (M=3.56) among others. It is recommended to resolve the natural resource conflicts which can be achieved by equal distribution of resources, clear rights to resources and good land governance.